Management of bi-canalicular block: A novel technique - Manju Meena; Milind Naik; Santosh Honavar (Indian Journal of Plastic Surgery)
Medial canthal dystopia with canalicular obstruction is a common presentation following injury to the medial canthal region. Conjunctivodacryocystorhinostomy with Lester′s Jones tube is considered as the standard treatment in such cases. Alternatively, these patients can be managed by retrograde intubation dacryocystorhinostomy with medial canthoplasty. We herein describe the modification of retrograde bicanalicular intubation, combined with medial canthoplasty (monopedicle flap) which gives good cosmetic results.